Djelantik’s Aesthetic Study in the Visual Poster “Every Flower Tells a Story” - Haniyah Ashillah Putri; Mukhsin Patriansah; Tria Puspa Selomita; Muhammad Ridwan (Acintya, 2025)
A poster is a visual communication medium that effectively conveys messages through a combination of design elements such as images, colors, and text. The purpose of this study is to examine the effectiveness of the poster titled "Every Flower Tells a Story," created by Shalyna, a student at Indo Global Mandiri University (UIGM) in 2025. The poster conveys meanings of growth and self-uniqueness through floral symbolism, utilizing the distinctive aesthetics of the Y2K era. A retro-futuristic style is presented through a neon color palette, varied typography with digital effects, and decorative elements such as stars and dynamic lines. The urgency of this study lies in the need to evaluate how visual constructions adopting the digital nostalgia of the 2000s can influence the perception and emotional engagement of contemporary audiences. This research employs a descriptive qualitative method with visual and formal analysis approaches. Data collection techniques include in-depth interviews with the creator, observation of the creative process, and a literature review on design theory and aesthetics. The collected data were analyzed using an aesthetic theoretical approach based on the theories A.A.M. Djelantik, which examine the relationship between visual elements and the meanings embedded in the poster. The findings indicate that the poster successfully integrates Y2K digital nostalgia aesthetics with a cohesive combination of bright colors, experimental typography, floral illustrations, and futuristic ornaments. The fusion of visual and verbal signs in the poster reinforces the message of self-acceptance and appreciation for individual growth processes. Based on these results, it is hoped that this research can contribute academically to the development of visual communication design and inspire the public to better understand and appreciate strategic and relevant aesthetic messages within the context of meaningful communication.